Intramolecular hydrogen bonds and structural nonrigidity of pyrimidine nucleosides - Mishchuk, Y.R.; Hovorun, D.M. (Биополимеры и клетка, 1998)
Optimal structures and intramolecular web of H-bonds of cytidinc, undine, thymidine, 1heir deoxyribo-analogues and some O5'-, O3'-deutero derivatives were studied by means of MNDOl H semiempirical quantum-chemical method. Effect of the intramolecular H-bonda on the slereochemical structure of nucleosides (particularly, on the stabilization of anti conformation), on the physico-chemical characteristics of nucleoside molecules (heat of formation, dipolc moment, first adiabatic ionization potential and the charge distribution), and on the dynamical characteristics of pyrimidine nucieosides (barriers of the interconvertion, frequencies of the torsional vibrations) was elucidated. The intramolecular 11-bonds in polynudeolides and their influence on the nucleic acid architecture, and nonlinear dynamic properties arc discussed. Оптимізовані структури цитидину, уридину і тимідину, їхніх дезоксирибо-аналогів та деяких О5', О3'-депротонованих похідних отримані за допомогою напівемпіричного квантовохімічного методу MNDO/H. Виявлено сітки внутрішньомолекулярних водневих зв'язків піримідинових нуклеозидів та вивчено їхній вплив на. стереохімічну структуру молекул (зокрема, на стабільність anti-конформації), фізико-хімічіні параметри /теплоту утворення, дипольний момент, потенціал, іонізації та розподіл зарядів), а також на динамічні характеристики піримідинових нуклеозидів (бар'єри інтер конверсії, частоти торсійних коливань). Обговорюється присутність внушріишьомолекулярних водневих зв'язків у полі нуклеоіпидах та їхнє значения у формуванні, структури та нелінійної динаміки нуклеїнових кислот. Оптимизированные структуры цитидина, уридина и тимидина, их дезоксирибо аналогов и некоторых О5'-, О3’ -депротонированных производных получены с помощью полуэмпирического квантовохиминеского метода. MNDO/H. Обнаружены сетки внутримолекулярных водородных связей пиримидиновых нуклеозидов и исследовано их влияние на стереохимическую структуру молекул с в частности, на стабильность anti-конформации), физико-химические параметры (теплоту образования, дипольный момент, потенциал ионизации и распределение зарядов), а также на. динамические характеристики пиримидииовых пуклеозидов (барьеры интерконверсии, частоты торсионых колебании). Обсуждается наличие внутримолекулярных водородных связей в полинуклеотидах и их значение в формировании структуры и нелинейной динамики нуклеиновых кислот.